TỔNG HỢP, ĐẶC TRƯNG VÀ ỨNG DỤNG VẬT LIỆU NANO-ZEOLIT NaX TỪ CAO LANH II - TỔNG HỢP VÀ ĐẶC TRƯNG VẬT LIỆU NANO-ZEOLIT NaX TỪ CAO LANH KHÔNG XỬ LÝ AXIT- ẢNH HƯỞNG CỦA PHƯƠNG PHÁP XỬ LÝ NGUYÊN LIỆU VÀ HÀM LƯỢNG NƯỚC TRONG GEL ĐẾN KÍCH THƯỚC TINH THỂ - Lan Anh, Hà Thị; Đôn, Tạ Ngọc (Vietnam Journal of Chemistry, 2012)
Nano-zeolite NaX has been synthesized from Phu Tho kaolin without acid treating step. Influence of raw materials treating method and water content in gel on crystal size have been investigated. Results obtained from XRD, IR, SEM, TEM, TG/DSC show that nano-zeolite NaX has crystallinity of 95%, specific surface area of 573m2/g (with outer surface area of 92 m2/g), crystal size of 25nm, thermal stability up to 798oC. Without acid treating step, the surface area is higher but pore size in mesoporous range and crystal size is larger. Increasing water content in gel makes crystal size increasing sharply.